(untitled) (Comprehensive Journal of Science, 2025)
Patients with Down syndrome present unique challenges during general anesthesia due to their anatomical and physiological characteristics. This cross-sectional study investigates the rate and nature of anesthesia-related complications in 30 Down syndrome patients across three hospitals in Tripoli-Libya. The findings reveal high rates of congenital heart defects (70%), intraoperative awareness (66.7%), and intubation difficulties (43.3%). Sevoflurane and propofol were the most commonly used anesthetic agents. The study highlights the need for specific anesthesia protocols and enhanced preoperative assessment to reduce risks in this vulnerable population